Design of Compensation System Using Adhered Method and Overlapping Method at PT XY DKI Jakarta - Indah Wahyuningsih; Kartika Wulandari Sulaiman; Nofita Setyani; Elvina Dian Paramita; Kamilla Azzahra (Ridwan Institute, 2022)
Compensation is one of the essential factors that can motivate employees to improve performance. Compensation provided by the company must be comparable to the company's workload, job risk, and the competencies that accompany the position. The Company is obliged to provide compensation both financially and non-financially so that employees' standard of living needs can be met. Therefore, it is necessary to design an appropriate compensation system based on the value of the job (job value). The object of this study is XY Company, located in DKI Jakarta. XY company is engaged in education, namely online English courses and early childhood tutor franchise, as well as in the culinary field, namely online courses in the pasta pizza business. The research methods used are quantitative and qualitative methods sourced in scientific journals and trusted articles. This research focuses on the compensation system. The method of processing and analyzing data used to compile the job value and job grading-based compensation system in XY companies is to use Compensable Factors analysis using hay method, Salary Mapping Adhered, and Salary Mapping Overlapping. This study shows that the effective compensation system to be implemented by PT XY is to use overlapping methods. The division of salary overlapping methods brings more benefits because the salary increase is less significant than the adhered method